Acquisition behaviours for nutrition‐related information based on a health promotion model for older adults in a long‐term care facility - Jing Liu; Huiping Li; Ying Xie; Yong Zhao; Qinghua Zhao; Mingzhao Xiao; Jun Wang; Huanhuan Huang (Wiley, 2023)
Abstract Aim To explore the acquisition behaviours for nutrition‐related information of older adults in a long‐term care facility. Design A qualitative descriptive design was used in this study. Methods Sixteen older adults in a long‐term care facility were recruited using purposive sampling between March and May 2021. Data were collected via face‐to‐face semi‐structured interviews, based on open questions regarding acquisition behaviours for nutrition‐related information and flexible question formulation, and the data were analysed using an inductive-deductive method. A health promotion model was used as a conceptual framework to regulate the refinement of themes. Results Three themes were identified in this study. The first theme discussed the individual characteristics and experiences of older adults that contributed to their acquisition behaviours for nutrition‐related information. The second theme described behaviour‐specific cognitions of and the effects on the participants regarding the influencing factors involving various internal individual elements and external physical environment. The third theme explored the positive behavioural outcomes of the participants resulting from these acquisition behaviours. Conclusion Acquisition behaviours for nutrition‐related information of older adults in long‐term care facilities were affected by both individual characteristics and external physical environment factors. Access to nutritional information can help older adults cultivate a healthy diet. Although they exhibited a significant interest in nutrition, the participants still encountered several difficulties. Based on the actual care needs of the older people, appropriate nutritional information interventions should be provided by healthcare providers working in long‐term care facilities so as to improve the ability of the older people to acquire information independently. Patient or public contribution All 16 participants actively participated in the interview process and the preliminary preparation of the article.